The degradation of chicken feathers by Ochrobactrum intermedium results in antioxidant and metal chelating hydrolysates and proteolytic enzymes for staphylococcal biofilm dispersion - de Menezes, Cíntia Lionela Ambrosio [UNESP]; Boscolo, Maurício [UNESP]; da Silva, Roberto [UNESP]; Gomes, Eleni [UNESP]; da Silva, Ronivaldo Rodrigues [UNESP] (Springer Nature, 2023)
The increase in the generation of chicken feathers, due to the large production of the poultry industry, has created the need to search for ecologically safer ways to manage these residues. As a sustainable alternative for recycling keratin waste, we investigated the ability of the bacterium Ochrobactrum intermedium to hydrolyze chicken feathers and the valorization of the resulting enzymes and protein hydrolysate. In submerged fermentation with three different inoculum sizes (2.5, 5.0, and 10.0 mg of bacterial cells per 50 mL of medium), the fastest degradation of feathers was achieved with 5.0 mg cells, in which a complete decomposition of the substrate (96 h) and earlier peaks of keratinolytic and caseinolytic activities were detected. In the resulting protein hydrolysate, we noticed antioxidant and Fe2+ and Cu2+ chelating activities. ABTS scavenging, Fe3+-reducing ability and metal chelating activities of the fermentative samples followed the same trend of feather degradation; as feather mass decreased in the media, these activities increased. Furthermore, we noticed about 47% and 60% dispersion of established 7-day biofilms formed by S. aureus after enzymatic treatment for 5 h and 24 h, respectively. These findings highlight the potential use of this bacterium as an environmentally friendly alternative to treat this poultry waste and offer valuable products.
Keywords: Feather; Keratinolytic enzyme; Peptidase; Protease; Staphylococcus aureus